Hydrochemical assessment of Chehelchai river water, Golestan province for drinking and agricultural purposes - Mohammad Gholizadeh; Mohammad Zibaei (سلامت و محیط, 2020)
Background and Objective: Surface water is usually highly variable in chemical composition due to contact with different geological formationsand other surface and groundwater resources.  Knowledge on water quality and the impact of human activities are particularly important for sustainable management and planning of water resources. The aim of this study was to investigate the physicochemical and hydrochemical quality of Chehelchai river water in Golestan province. Materials and Methods: In this study, 6 sampling stations were selected based on standard criteria including land use type, accessibility and standard distributions along the river in 2018. 10 river water quality parameters including pH, electrical conductivity, total soluble solids, sulfate, chloride, bicarbonate, sodium, potassium, calcium and magnesium - were measured according to standard methods for one year period. Piper, Schuler, Durov, Wilcox and Gibbs diagrams were applied for hydrochemical analysis using RockWorks.17 software.  Statistical analysis was performed using one-way ANOVA. Results:  Results indicated the abundance of major ions was found in the order of HCO3- > SO42- > Cl- and Ca2+ > Na+ > Mg2+ > K+. The river water type was predominantly determined as calcic bicarbonate. The findings revealed that the water of the study area is acceptable for drinking purpose based on Schuler diagram and also appropriate for agricultural uses considering Wilcox diagram (80% of the samples in class S1-C3 (saline - usable for agriculture)) and the average sodium uptake ratio (0.79). Conclusion: The presence of dolomite ores, the absence of factories and domestic sewage and adhering to hygiene regulations by the residents, are the main reasons which have increased the quality of Chehelchai river water.